2020
DOI: 10.1101/2020.07.19.211201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving cell-free glycoprotein synthesis by characterizing and enriching native membrane vesicles

Abstract: Cell-free gene expression (CFE) systems from crude cellular extracts have attracted much attention for accelerating the design of cellular function, on-demand biomanufacturing, portable diagnostics, and educational kits. Many essential biological processes that could endow CFE systems with desired functions, such as protein glycosylation, rely on the activity of membrane-bound components. However, without the use of synthetic membrane mimics, activating membrane-dependent functionality in bacterial CFE systems… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…In parallel, S12 extracts were prepared from E. coli CLM24 cells that simultaneously overexpressed Cj PglB and the C. jejuni glycan biosynthesis enzymes. Our previous work demonstrated that such extracts are selectively enriched with both Cj PglB and Cj LLOS 17 and that S12 extract can achieve higher glycosylation efficiencies than S30 extract due to its increased concentration of vesicle-bound glycosylation machinery 19 . To generate glycoRNC complexes, batch-mode sequential CFGpS reactions were performed by priming glycoenriched extracts with plasmid DNA encoding the Im7 N58 –SecM17 construct, which induced translation and subsequent stalling of Im7 N58 –SecM17 on 70S ribosomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, S12 extracts were prepared from E. coli CLM24 cells that simultaneously overexpressed Cj PglB and the C. jejuni glycan biosynthesis enzymes. Our previous work demonstrated that such extracts are selectively enriched with both Cj PglB and Cj LLOS 17 and that S12 extract can achieve higher glycosylation efficiencies than S30 extract due to its increased concentration of vesicle-bound glycosylation machinery 19 . To generate glycoRNC complexes, batch-mode sequential CFGpS reactions were performed by priming glycoenriched extracts with plasmid DNA encoding the Im7 N58 –SecM17 construct, which induced translation and subsequent stalling of Im7 N58 –SecM17 on 70S ribosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Since this early pioneering work, diverse proteins of prokaryotic and eukaryotic origin have been N-glycosylated in engineered E. coli cells carrying the pgl glycosylation pathway [12][13][14] or other heterologous glycosylation pathways 15,16 . More recently, glycoengineered E. coli have been leveraged as source strains to provide cell-free extracts selectively enriched with protein glycosylation machinery, including OSTs and LLOs [17][18][19][20][21][22][23][24] . Upon addition of cofactors and plasmid DNA encoding an acceptor protein of interest, these glyco-enriched cell-free extracts enable a one-pot reaction scheme for site-specific expression and glycosylation of target glycoproteins at relatively high titers.…”
Section: Introductionmentioning
confidence: 99%
“…The key idea is that OST and LLOs are overexpressed in the E. coli cells, enriching the crude extract with these components and obviating the need for exogeneous addition of purified components. Glycosylation components are present in E. coli extracts in nanoscale [ 48 ] membrane vesicles which serve the dual purpose of enabling (i) the activation of ATP regeneration through oxidative phosphorylation [ 61 ] and (ii) harboring active membrane-bound LLOs and OSTs [ 57 ]. Glycoengineered extracts of E. coli have been used to synthesize a variety of glycoproteins, such as EPO, with diverse glycan structures (Table 1 ).…”
Section: Ost-dependent Glycosylation In Glycoengineered E mentioning
confidence: 99%
“…iVAX glycoconjugate titers (Table 1 ) enable individual vaccine doses of 10 μg to be produced in one hour for ~ $6 [ 133 ]. In efforts to further decrease biomanufacturing costs, E. coli CFGpS was recently optimized to synthesize glycoprotein titers of > 100 μg/mL in batch by increasing the concentrations of the LLO- and OST-harboring vesicles during extract preparation [ 48 ].…”
Section: Ost-dependent Glycosylation In Glycoengineered E mentioning
confidence: 99%
See 1 more Smart Citation